ANALYSIS OF BANKING EFFICIENCY USING THE DEA (DATA ENVELOPMENT ANALYSIS) METHOD AT MESTIKA BANK WHICH IS LISTED ON THE INDONESIA STOCK EXCHANGE - Cindy Jessica; Thomas Sumarsan Goh; Elidawati Elidawati (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
Bank Mestika is a private city bank domiciled in the city of Medan. Initially, Bank Mestika's efficiency performance evaluation was measured using financial ratios, but according to some experts the efficiency assessment could not be done partially but had to take into account all existing outputs and inputs. The purpose of the study was to find out how the level of efficiency of Bank Mestika is based on the size of the bank as seen from total assets using the Data Envelopment Analysis (DEA) approach. In this study, the object of research is banking efficiency, which is assessed by the size of the bank measured by total assets, BOPO is measured from interest income, interest expense, while ROA is measured from profit before tax with total assets. The Data Envelopment Analysis (DEA) method is used to measure banking efficiency in 2020 at Bank Mestika which is listed on the Indonesia Stock Exchange. The results show that Bank Mestika Dharma, Tbk is also facing inefficiency, meaning that the economic activity unit has not been able to allocate its resources optimally. The DEA approach can see the source of inefficiency by measuring the potential improvement of each input.